Attachment 25610

I let (x+1)=x and (x-3)=y and I got

where do I go from here?

Printable View

- Nov 9th 2012, 09:49 PMkingsolomonsgraveHow to simplify this expression
Attachment 25610

I let (x+1)=x and (x-3)=y and I got

where do I go from here? - Nov 9th 2012, 10:02 PMMarkFLRe: How to simplify this expression
Rewrite the denominator as and divide out the factor common to the numerator and denominator.

- Nov 10th 2012, 06:39 AMSorobanRe: How to simplify this expression
Hello, kingsolomonsgrave!

Quote:

I let (x+1)=x and (x-3)=y. . Don't do that!

Use two "new" variables: .

and I got

where do I go from here?

You can cancel the x's . . . and back-substitute.

We have: .

Factor: .

Reduce: .

Simplify: .

Where did this problem come from?

If it came from an application of the Quotient Rule,

. . something is drastically wrong.